Temperature inversions and stable layers near ground over India - SIVARAMAKRISHNAN, M. V.; MOKASHI, R. Y.; PARAMESWARAN, N. V. (MAUSAM, 1972)
Change in air temperature with altitude in the lowest layers of the atmosphere is an important consideration in the incidence of air pollution. The paper gives basic information on ground inversions including isothermal layers and those with lapse rates lea" than 2°C/km near the ground utilising daily radiosonde data of 16 Indian stations. The frequency of ground inversions over India south of latitude 18°N is very law as compared to the northern stations. The ground inversions form nearly a daily feature at almost all the northern stations during the months November to February. The frequency increases very considerably by including under ground inversions, layers which are isothermal or have a lapse rate less than 2"C/km. The most frequent thickness of ground inversion is in the range of 201-500 metres. Lapse rates of the order of I to 10°C/km are observed on 50 per cent of the occasions over the northern parts of the country. Over the Southern parts, however, this percentage is higher and is of the order of 85.